Investigating the action model of the resistance enhancement induced by bacterial volatile organic compounds against Botrytis cinerea in tomato fruit - Chen, Jianhua; Cao, Kexin; Lu, Xuan; Huang, Ding; Ming, Ruhong; Lu, Rumei; Huang, Rongshao; Li, Liangbo (Frontiers in Plant Science, 2024)
Inducing natural resistance against pathogen infection in postharvest tomatoes is a sustainable strategy for reducing postharvest losses. This study aimed to determine the the action model of the resistance enhancement induced by bacterial volatile organic compounds (VOCs) against Botrytis cinerea. The results showed that the application of VOCs inhibited the damage to tomato fruits caused by B. cinerea. VOCs treatment had remarkable beneficial effects on the activities of the main defence-related enzymes, including chitinases, glucanases, peroxidases, ascorbate peroxidases, polyphenol oxidases, and phenylalanine ammonia-lyases. The expression of response genes involved in salicylic acid and jasmonic acid biosynthesis and signalling pathways was enhanced upon VOCs treatment. Metabolomics data demonstrated that VOC treatment triggered the accumulation of phenolic acids, including substrates in phenolic acid biosynthesis pathways, hydroxycinnamic acid, hydroxybenzoic acid, and their derivatives. Transcriptomics analysis and qRT-PCR verification revealed that VOCs treatment significantly upregulates the expression of core genes related to phenolic acid biosynthesis, specifically in shikimate pathway (SlDAHPS, SlSDH, SlCS, and SlADT3) and phenylalanine metabolic pathway (SlPAL, Sl4CL, SlBAHD1, SlCYP98A2 and SlCAP84A1). Taken together, our findings suggest that VOCs enhanced tomato fruit postharvest resistance against B. cinerea by regulating defence enzyme activity, SA/JA signalling, and phenolic acid biosynthesis pathway. This study provides new insights into the mechanisms by which VOCs fumigation manages postharvest grey mould in tomatoes.